2019
DOI: 10.2147/dddt.s199572
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dexmedetomidine protects PC12 cells from lidocaine-induced cytotoxicity via downregulation of Stathmin 1</p>

Abstract: Background: Understanding of lidocaine-induced neurotoxicity is not complete, resulting in the unsuccessful treatment in some clinical settings. Dexmedetomidine (DEX) has been shown to alleviate lidocaine-induced neurotoxicity in our previous cell model. However, the rationale for DEX combined with lidocaine to reduce lidocaine-induced neurotoxicity in the clinical setting remains to be further clarified in the detailed molecular mechanism. Methods: In this study, we establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…[31][32][33][34] In recent years, researchers found that DEX inhibited lidocaine-induced neurotoxicity. 16,17,23 In this study, we also verified the role of SIRT1/FOXO3a signaling in the effect of DEX on lidocaine-induced neurotoxicity. We found that DEX concentration-dependently inhibited lidocaine-induced decrease in SIRT1 and increase in FOXO3a and suppressed the increase in acetylation of FOXO3a mediated by reducing SIRT1.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…[31][32][33][34] In recent years, researchers found that DEX inhibited lidocaine-induced neurotoxicity. 16,17,23 In this study, we also verified the role of SIRT1/FOXO3a signaling in the effect of DEX on lidocaine-induced neurotoxicity. We found that DEX concentration-dependently inhibited lidocaine-induced decrease in SIRT1 and increase in FOXO3a and suppressed the increase in acetylation of FOXO3a mediated by reducing SIRT1.…”
Section: Discussionsupporting
confidence: 67%
“…20,21 Several studies have found that DEX exhibits a neuroprotective effect in the lidocaine-induced model of neurotoxicity. 16,[21][22][23] However, the mechanism of DEX-related protective effects in lidocaineinduced neurotoxicity is still not completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In a recent study, 150 μM was the maximum safe concentration for DEX in PC12 cells, and 50 μM was eventually selected for the subsequent experiments. 51 Other studies used DEX 50 ng/mL (equivalent to 250 nM) on pacemaker cells in sinoatrial nodes of rabbits and DEX 200 ng/mL (equivalent to 1 µM) on rat ventricular myocytes. 48,52 Therefore, it is possible that the safe concentration of DEX varies in different species and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, by upregulating SIRT/FOXO3a signaling 24 as well as by inhibiting Stathmin-1/Bcl-2/Caspase-9/Caspase-3 mediated lidocaine-induced neurotoxicity, 25 dexmedetomidine used in conjunction with lidocaine may provide additional anti-inflammatory benefits, while improving the safety profile of lidocaine.…”
mentioning
confidence: 99%